El turno, un espacio de diversión en Costa Rica, 1890-193 - Enríquez Solano, Francisco (2004)
The article asserts the origins, historical trajectory, and characteristics of one of the most popular festivities in Costa Rica, the so-called turnos, in the period between 1890 and 1930. This novel investigation analyzes elements associated with popular religious practices, sociability, and national identity, without excluding certain local features, since the origin of these popular festivities dates back to the colonial Cofradías.